Building Madrasah Work Culture through Transformative Leadership Based on Religious - Mawardi, Mawardi; Hambali, Hambali; Hidayat, Husni (JURNAL AL-TANZIM, 2023)
This article aims to analyze and understand religious-based transformative leadership in building a work culture in madrasah. In this era, Islamic cultures are increasingly being eroded by the emergence of Western culture, thus requiring transformation from a leader in addressing existing problems. This research was conducted at the Sarolangun State Madrasah Aliyah, Jambi, with a descriptive-qualitative approach. Observations, interviews and documentation were carried out to obtain valid data. The study results a show that religious-based transformative leadership in building a work culture in madrasah is carried out through; madrasah principal commitment, consolidation of human resources, habit forming, and follow-up evaluation. This research has implications for the importance of a work culture built by a leader based on cultural roots and religious values so that what is sought becomes material values and worship.